2012
DOI: 10.1534/genetics.112.145524
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of a Violation of Dollo’s Law: Re-Evolution of Rotating Sex Combs inDrosophila bipectinata

Abstract: Phylogenetic analyses suggest that violations of "Dollo's law"-that is, re-evolution of lost complex structures-do occur, albeit infrequently. However, the genetic basis of such reversals has not been examined. Here, we address this question using the Drosophila sex comb, a recently evolved, male-specific morphological structure composed of modified bristles. In some species, sex comb development involves only the modification of individual bristles, while other species have more complex "rotated" sex combs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…For more than a century, trait reversal after a loss event has been thought to be highly unlikely; Dollo's law of irreversibility states that, once a trait is lost, it is unlikely for the same trait to be found in a descendant lineage, thereby excluding certain evolutionary paths 5,6 . Despite this purist interpretation, many examples of apparent violations to Dollo's law have been documented [7][8][9][10][11][12][13][14][15] , and it is clear that evolutionary processes sometimes break Dollo's law [16][17][18] . Nonetheless, the molecular and genetic mechanisms leading to trait reversal have only been determined in a few cases 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…For more than a century, trait reversal after a loss event has been thought to be highly unlikely; Dollo's law of irreversibility states that, once a trait is lost, it is unlikely for the same trait to be found in a descendant lineage, thereby excluding certain evolutionary paths 5,6 . Despite this purist interpretation, many examples of apparent violations to Dollo's law have been documented [7][8][9][10][11][12][13][14][15] , and it is clear that evolutionary processes sometimes break Dollo's law [16][17][18] . Nonetheless, the molecular and genetic mechanisms leading to trait reversal have only been determined in a few cases 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…Dollo describes evolution as "irreversible" and "discontinuous," and trait complexity prevents evolution from returning organisms to their previous state. Few studies have actually turned to the molecular mechanisms determining trait function (Sassi et al 2007;Christin and Besnard 2009;Seher et al 2012), or the selective forces shaping traits. These studies infer the re-evolution of traits after ancestral loss, sometimes multiple times.…”
mentioning
confidence: 99%
“…Those analyses remain controversial, however, as unsuitable inference methods have been used, and the true complexity of traits is often ignored (Goldberg and Igić 2008). Few studies have actually turned to the molecular mechanisms determining trait function (Sassi et al 2007;Christin and Besnard 2009;Seher et al 2012), or the selective forces shaping traits. Here, we analyze the molecular evolution of a mammalian chemosensory system, examining changes in selection underlying the loss of this complex system throughout the diversification of bats.…”
mentioning
confidence: 99%
“…Conversely, it may be found that the promoter regions or other regulatory complexes responsible for eggshells are simply switched off during the transition to viviparity, but are maintained by selection in a functional or dormant state in the genome of viviparous lineages, and need only be reactivated or re‐formulated for the eggshell to be regained. Such a process (re‐activation of functional gene‐complexes) has been commonly reported as a mechanism for the regain of complex traits in other organisms, such as sex combs in Drosophila (Seher et al, ), hand musculature in primates (Diogo and Wood, ), and sexuality in oribatid mites (Domes et al, ).…”
mentioning
confidence: 99%